The crisis in Ukraine and its impact on global food security - Bohdaniuk, Olena; Voliak, Lesia; Bohdaniuk, Oleksandr (Turystyka i Rozwój Regionalny, 2022)
Ukraine has been playing an increasing role on the world agricultural market. Only two decades ago Ukraine’s grain exports were equivalent to feeding 40 million people, and already more than 400 million today. In 2019–2021 Ukraine accounted for nearly 10% of global wheat and 15% of corn exports, 15% of barley exports and nearly 50% of sunflower oil exports Russia’s invasion of Ukraine amplified the role of Ukraine in ensuring global food security. Blocked exports and endangered current planting campaign in Ukraine surged world market prices and risked not only to undermine country’s agri-food sector and overall economy, but also to starve hundreds of millions globally. In this article, the authors tried to provide an assessment of the importance of Ukraine as a world producer of agricultural products and the main losses and problems in connection with Russia’s invasion, both for Ukraine and for the world.